2018
DOI: 10.1111/hex.12674
|View full text |Cite
|
Sign up to set email alerts
|

Personal strengths reported by people with chronic illness: A qualitative study

Abstract: BackgroundSelf‐management of chronic illness can be highly demanding and people need to mobilize their personal strengths to live well with their condition. More knowledge is needed about how people with chronic illness perceive and use their personal strengths as a basis for better integrating empowering person‐centred approaches into health care.ObjectiveTo explore what people with chronic illness describe as their strengths relevant to their health and well‐being.Setting and ParticipantsThirty‐nine particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 47 publications
4
56
0
Order By: Relevance
“…It has been postulated that this added challenge to identity reconstruction exacerbates the negative mental health implications from LTCs for young adults. 23,39. The present findings fit well with the concept of biographical disruption 28 to the value of positive thinking (eg Refs 8,11,17,23,26 ).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…It has been postulated that this added challenge to identity reconstruction exacerbates the negative mental health implications from LTCs for young adults. 23,39. The present findings fit well with the concept of biographical disruption 28 to the value of positive thinking (eg Refs 8,11,17,23,26 ).…”
Section: Discussionsupporting
confidence: 87%
“…This also expands on previous research which has identified reaching acceptance of new/altered identities as important for mental health, and was also seen as a long and difficult process that required time and reflection (eg Refs). The other suggestions made by participants in the present study are less present in the existing literature, although some reference has previously been made to the value of positive thinking (eg Refs).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Studies have shown that when dedicated to health and well-being, people with obesity develop multifaceted coping mechanisms for dealing with stigma and misunderstanding from society (Bombak, 2015;Puhl & Brownell, 2003). Hence, a holistic approach is considered to optimize health and well-being among people with obesity by turning attention towards their own resources to strengthen empowerment and well-being (Borge, Christiansen, & Fagermoen, 2012;Brown & Wimpenny, 2011;Knutsen, 2012: Kristjansdottir, Stenberg, Mirkovic, Krogseth, Ljoså, Stange & Ruland, 2018.…”
Section: Introductionmentioning
confidence: 99%